1987
DOI: 10.1007/bf00203576
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring monoterpenoids in needles of Picea abies (L.) Karst

Abstract: Summary. An analysis was made of the effects of different sampling and extraction techniques on the amounts and pattern of monoterpenoids isolated from needles of Norway spruce. The following isolation and analysis procedure was finally adopted: liquid nitrogen-cooled needles were pulverized by a microdismembrator, extracted with pentane overnight at 2 ~ -3~ and concentrated to a volume not less than 3 ml/g fresh weight on a Vigreux column. The crude extract was injected splitless (with solvent split) onto a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The relatively small increase in terpene accumulation in needles was not accompanied by any significant changes in terpene composition, unlike in stems. The major needle monoterpenes detected in this study were similar to those previously reported for Norway spruce (Schö nwitz et al, 1987;Persson et al, 1993Persson et al, , 1996Paule and Yazdani, 1992;Holubova et al, 2000) and correspond to compositional type 1b (high limonene, low myrcene, and high bornyl acetate) as described by Schö nwitz et al (1990a). The elevated levels of monoterpenes and sesquiterpenes after MeJA spraying peaked 15 d after treatment but declined to control levels rapidly after that, probably as a result of volatilization or catabolism.…”
Section: Induced Terpene Accumulation In Needles Is Much Lower Than Isupporting
confidence: 88%
See 1 more Smart Citation
“…The relatively small increase in terpene accumulation in needles was not accompanied by any significant changes in terpene composition, unlike in stems. The major needle monoterpenes detected in this study were similar to those previously reported for Norway spruce (Schö nwitz et al, 1987;Persson et al, 1993Persson et al, , 1996Paule and Yazdani, 1992;Holubova et al, 2000) and correspond to compositional type 1b (high limonene, low myrcene, and high bornyl acetate) as described by Schö nwitz et al (1990a). The elevated levels of monoterpenes and sesquiterpenes after MeJA spraying peaked 15 d after treatment but declined to control levels rapidly after that, probably as a result of volatilization or catabolism.…”
Section: Induced Terpene Accumulation In Needles Is Much Lower Than Isupporting
confidence: 88%
“…In Norway spruce and other conifers, terpenes are accumulated not only in stems but also in needles (Schö nwitz et al, 1987;Schö nwitz et al, 1990a;Persson et al, 1996). However, much less is known about the biochemical regulation of terpene formation and accumulation in conifer needles.…”
mentioning
confidence: 99%
“…Extraction of diterpenoid resin acids from plant tissues is generally achieved using relatively polar solvent mixtures (e.g. CHC1,-MeOH), whereas the isolation of monoterpenes is achieved by steam distillation or extraction with relatively non-polar solvents such as pentane or diethyl ether (Schonwitz et al, 1987;Muzika et al, 1990). Because methyl tert-butyl ether (MTBE) has been shown to be an excellent solvent for the extraction of resin acids from paper mill waste ( Voss and Rapsomatiotis, 1985), we tested this solvent for the simultaneous extraction of both diterpenoid resin acids and monoterpene olefins from fresh lodgepole pine stems.…”
Section: Resultsmentioning
confidence: 99%
“…To properly model the real response, the pool size and the rate of the replenishment of the pools must in principle be known. However, the pool size can generally be assumed to be infinite, because theoretically, the pool capacity is high enough to sustain a constant emission of 1 µg h −1 g −1 dw over 1500 h at 30 • C based on a MT content of about 900 µg g −1 needle fresh weight of Picea abies (Schönwitz et al, 1987) assuming a needle water content of 50 % (Schmidt, 1953).…”
Section: Environmental Correction Factors γmentioning
confidence: 99%